Desenvolvimento de têxteis biofuncionais com β-CD para a incorporação de fármacos fotodinâmicos - Firmino, Helen Beraldo (2022)
The use of biopolymers such as cyclodextrins in textiles for the development of biofunctional fabrics is an alternative for the development of eco-friendly textiles. Cyclodextrins can create interactions with the chemical groups available in cotton, allowing the functionalization of the fabric and the complexation of active molecules that will be released, such as the dyes Erythrosine B and Methylene Blue. These dyes have the photodynamic ability to yields singlet oxygen (1O2), causing cell death in some pathogen microorganisms eventually present in human skin. Therefore, this study presents the formation of a biofunctionalized cotton fabric that when activated by light generates photoactive species that may possess antimicrobial or antifungal characteristic, for cosmetic or medical purposes. The obtained materials were characterized by Scanning Electron Microscopy (SEM), Attenuated Reflection Fourier Transform Infrared Spectroscopy (FTIR-ATR), Determination of Dyeing Variables and Functionalization of Cotton Fabric, Grafiting, Colorimetry, UV-VIS Spectrophotometry Microbiological Analysis, Photodegradation Assays, Release Kinetics of Erythrosine B and Methylene Blue and ABDA Degradation Kinetics. With this, the work presents a textile that offers the combination of antimicrobial factors responsible for better healing of human skin wounds in a cotton fabric. It is therefore believed that the present study can paving the way for the development of antimicrobial fibers in order to design smart bandages.